2010
DOI: 10.1021/cm902989f
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Ligand-Dependent Cellular Interaction, Subcellular Localization, and Cytotoxicity of Polymer-Coated Quantum Dots

Abstract: Nanoparticle- and quantum-dot (QD)-based bioprobes are emerging as alternatives to small-molecule probes for in vitro and in vivo applications. However, their cellular interaction and cell uptake mechanism are significantly different from those of small-molecule probes and are extremely sensitive to surface ligands. These present a barrier in the development of nanoparticles and QDs as cellular probes. This work focused on the synthesis of various functionalized QDs with tunable surface charge, hydrophobicity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
164
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(172 citation statements)
references
References 70 publications
5
164
0
Order By: Relevance
“…The active transport systems play a key role in the intracellular transport of macromolecules and NP. Extensive studies have shown that NP internalization mainly occurs via endocytotic pathways and depends on NP properties (e.g., size, charge, functionalization) as well as on the cellular origin and physiology (Kelf et al 2010;Pi et al 2010;Tan et al 2010). Some authors report presence of transtrophoblastic channels which are thought to be membrane-lined tubular systems that originate from membrane invaginations of the basal syncytiotrophoblastic surface and cross the cell towards its apical surface (Kertschanska et al 1997;Benirschke and Kaufman 2000).…”
Section: The Structure and Function Of The Placental Barriermentioning
confidence: 99%
See 3 more Smart Citations
“…The active transport systems play a key role in the intracellular transport of macromolecules and NP. Extensive studies have shown that NP internalization mainly occurs via endocytotic pathways and depends on NP properties (e.g., size, charge, functionalization) as well as on the cellular origin and physiology (Kelf et al 2010;Pi et al 2010;Tan et al 2010). Some authors report presence of transtrophoblastic channels which are thought to be membrane-lined tubular systems that originate from membrane invaginations of the basal syncytiotrophoblastic surface and cross the cell towards its apical surface (Kertschanska et al 1997;Benirschke and Kaufman 2000).…”
Section: The Structure and Function Of The Placental Barriermentioning
confidence: 99%
“…Nevertheless, the large NP used in the current reports have to be absorbed inside the trophoblast cells to be afterwards transferred to the fetal circulation. It is assumed that NP mainly enter the cells by the active transport, particularly, via the endocytotic pathways (Pi et al 2010;Tan et al 2010).…”
Section: The Possible Mechanisms Of Transplacental Transport Of Npmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the citrate-capped QDs might have little potential for biological labeling and imaging applications. On the other hand, there have been several researches reported on the great improvement of the ligand exchange procedures [14][15][16]. In this study, we are motivated to explore the possibility of TGA ligand transformation of CdTe QDs without affecting luminescent characteristics of the QDs to meet the future's demand for nanotoxicity studies and bioapplications.…”
Section: Introductionmentioning
confidence: 99%